EFFECT OF IRRIGATION AGENTS, ADHESIVE SYSTEM AND BOND STRENGTH OF COMPOSITE POST - Andonovska, Marija (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Evaluate the effect of irrigation agents, adhesive system and bond strength of composite post with the dentin. For this in vitro study, 48 single-rooted teeth were used, (incisions, second premolars with one root) extracted for orthodontic and periodontal reasons. The teeth were then divided into 2 groups of 24 teeth depending on the irrigation agent used, and each group was divided into 2 subgroups of 24 teeth depending on the cementation agent. After application of the composite post to the root canal and restoration, all samples were prepared in molds to test the strength of the composite post with the dentin. For this study, a descriptive statistical analysis was used, which was implemented on the obtained results, and was made in a statistical package Excel ANOVA 2016, where the test strength was done with Push-out testing. The results obtained were in favour of the group where 2.5% sodium hypochlorite and 17% EDTA were used as irrigants, where the technique of complete etching with 37% orthophosphoric acid was used, Excite adhesive (Ivoclar Vivadent Inc., Schaan, Liechtenstein) and dual-polymerizing cement Variolink II (Ivoclar Vivadent Inc., Schaan, Liechtenstein) the pressure, i.e. the bond strength obtained by push-out testing was the highest and was 2,185 MPa, and the weakest bond was obtained when we used only 2.5% sodium hypochlorite as an irrigant using Excite self-etching adhesive and SpeedCEMâ„¢ dual-polymerizing cement. From the results obtained from this study we can conclude that the bond between the composite post and the dentin is strongest with the application of the irrigants 2.5% sodium hypochlorite and 17% EDTA and the technique of complete etching with orthophosphoric acid in combination with Excite self-etching adhesive and SpeedCEMâ„¢ dual-polymerizing cement. Key words : endodontic treatment, irrigants, dual-polymerizing cements, composite post https://doi.org/10.55302/JMS2142122a